Thermal response to the surface heat flux in a macrotidal coastal region (Nuevo Gulf, Argentina) - Rivas, Andres Lujan (2016)
At mid-latitudes, sea water temperature shows a strong seasonal cycle forced by the incident surface heat flux. As depth decreases, the heat flux incidence is damped by the horizontal flux, which prevents the indefinite growth of the seasonal temperature range. In the present work, cross-shore transport in the west coast of Nuevo Gulf (Argentina) was analyzed. Processes tending to cool the coastal waters in summer and to warm the coastal waters in winter, were identified through temperature measurements, surface heat flux and tidal height. The simplified models proposed here provide a feedback mechanism that links changes in surface heat flux with changes in the horizontal heat flux during both seasons. On shorter time scales, tide produces significant variations in the height of the water column, therefore influencing temperature fluctuations and the direction of the horizontal flow.